Impact of Hunting on Large Mammal Densities in the West Indian Himalaya - , Hilaluddin; Khan, Daizy N.; Abbassi, Faiza (Indian Forester, 2011)
Game species are lost when forest areas are subjected to hunting and populations of already threatened species may become locally extinct from many such patches. The present study tested this hypothesis in the temperate forests of West Indian Himalaya. The animal densities were estimated in predetermined Belt Transects, whereas vegetation abundance was estimated using point count strategy. The study provides solid evidence that hunting seriously impacts populations of hunted species. The results show that barking deer (Muntiacus muntjak), goral (Nemorhaedus goral), Himalayan tahr (Hemitragus jemlahicus) and serow (Capricornis sumatraensis) are encountered more frequently in protected sites than hunted sites. The fate of globally threatened species, specifically Himalayan tahr and serow, seems to be heavily impacted; and, both species are at high risk of local extinctions from many forest patches in this landscape of the world.